2016
DOI: 10.1371/journal.pone.0162321
|View full text |Cite
|
Sign up to set email alerts
|

Targeting polyIC to EGFR over-expressing cells using a dsRNA binding protein domain tethered to EGF

Abstract: Selective delivery of drugs to tumor cells can increase potency and reduce toxicity. In this study, we describe a novel recombinant chimeric protein, dsRBEC, which can bind polyIC and deliver it selectively into EGFR over-expressing tumor cells. dsRBEC, comprises the dsRNA binding domain (dsRBD) of human PKR (hPKR), which serves as the polyIC binding moiety, fused to human EGF (hEGF), the targeting moiety. dsRBEC shows high affinity towards EGFR and triggers ligand-induced endocytosis of the receptor, thus lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Internalization of dsRNA induces the tumor to self-destruct by apoptosis, while activating immune modulatory pathways, leading to cytokine and chemokine induction. In addition to type I IFNs, we have detected RANTES, IP-10, GRO-α, IL-2, TNF-α, and IFN-γ (99,106,107). These molecules generate a "bystander effect" against the tumor: They are cytotoxic against tumor cells that do not themselves overexpress the receptor, boost tumor immunogenicity by increasing the expression of MHC-1 and tumor-specific antigens, and attract immune cells such as T cells and NK cells, which mount an attack against the tumor (100, 106, 108) (Fig.…”
Section: Targeting Polyinosinic/polycytidylic Acid To Tumorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Internalization of dsRNA induces the tumor to self-destruct by apoptosis, while activating immune modulatory pathways, leading to cytokine and chemokine induction. In addition to type I IFNs, we have detected RANTES, IP-10, GRO-α, IL-2, TNF-α, and IFN-γ (99,106,107). These molecules generate a "bystander effect" against the tumor: They are cytotoxic against tumor cells that do not themselves overexpress the receptor, boost tumor immunogenicity by increasing the expression of MHC-1 and tumor-specific antigens, and attract immune cells such as T cells and NK cells, which mount an attack against the tumor (100, 106, 108) (Fig.…”
Section: Targeting Polyinosinic/polycytidylic Acid To Tumorsmentioning
confidence: 89%
“…We have constructed both chemical and protein-based vectors that bind and carry polyIC to cancer cells that overexpress a membrane-bound receptor, such as the EGFR (Fig. 2) (99,100). PolyIC mimics viral dsRNA to provoke a profound antiviral attack.…”
Section: Targeting Polyinosinic/polycytidylic Acid To Tumorsmentioning
confidence: 99%
“…A previous study demonstrated that EGFR interacts with E-cadherin to promote proliferation by activating the MAPK pathway ( 39 ). Furthermore, patients with tumors bearing specific mutations in EGFR or overexpressing EGFR have a good clinical response to selective EGFR inhibitors ( 22 , 40 , 41 ). However, in a previous study, when the tumor cells developed resistance to the EGFR inhibitor, some cells exhibited mesenchymal characteristics and low EGFR expression, survived and underwent EMT ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that PKR has a high affinity for polyIC [52][53][54] and that isolated dsRBDs can facilitate the delivery of siRNA into cells [55]. Based on these reports we recently used the isolated dsRBDs to deliver polyIC to EGFtargeted cells successfully [56].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we had the additional complication that the dsRB domain binds host nucleic acids [57]. We designed a purification process incorporating an unfolding and re-folding protocol, SCP-N TTTACTCGAGCGGAGGTGCAGCTGCAGC SCP-C TTTTGCTCAGCGCCGTTACAGGTCC AGCCATG GFP-N TTTTCATATGGTGAGCAAGGGCG GFP-C TAAGGATCCGCCACCGCCGCTTTT CTTGTACAGC dsRB-N TTTCATATGATGGCTGGTGATC dsRB-C TTAGGATCCGCCACCGCCGCTCTCCGATAAGATC TGCAG 9ARG1 GATCCCGTCGTCGCCGTCGTCGCCGTCGCGGCCGCAA 9ARG2 AGCTTTGCGGCCGCGACGGCGACGACGGCGACGACGG Oncotarget 24055 www.impactjournals.com/oncotarget which successfully released the host nucleic acids [56]. We proved that the dsRB domain was functional using a gel mobility shift assay [58] (Figure 2C).…”
Section: Discussionmentioning
confidence: 99%